Urban food planning in Italian cities: a comparative analysis of the cases of Milan and Turin. Issue 8 (14th September 2017) - Calori, Andrea; Dansero, Egidio; Pettenati, Giacomo; Toldo, Alessia
ABSTRACT: This contribution explores the issue of urban food planning in the Italian context in a comparative perspective, basing on the case studies of Turin and Milan, the two main cities of Northern Italy, currently engaged in processes of urban food policies development. The first part of the article outlines the general structure of these tools and describes their role of new political spaces for a public debate about food policies. The second section comparatively analyses the two case studies stressing their differences and similarities. Finally, the conclusion of the article focuses on the importance of identifying the right scales for analyzing and planning food systems.